Rational Design of Nanostructured MnO2 Cathode for High-performance Aqueous Zinc Ion Batteries - Li, Qi; Zhao, Yajun; Wang, Yueyang; Khasraw, Abdalla Kovan; Zhao, Yi; Sun, Xiaoming (Chemical research in Chinese universities, 2023)
Aqueous Zn-MnO 2 batteries hold a promising potential for grid-scale energy storage applications due to their intrinsic safety, low fabrication cost, environmental friendliness and high theoretical energy densities. Developing novel nanostructured cathode materials with high discharge voltage, large capacity and excellent structural stability is one of the critical ways to achieve the high-performance aqueous Zn batteries. Enlighten by that, comprehending principles of materials design and identifying the challenges faced by the state-of-the-art MnO 2 hosts are vital preconditions. Rather than a simple comparison, this review mainly focuses on design strategies regarding to MnO 2 -based materials, including defect engineering, interfacial engineering, and pre-intercalation engineering. In addition, the energy storage mechanisms of MnO 2 -based cathodes are discussed to clarify the complicated chemical reactions during battery cycling. Challenges and perspectives are outlined to guide the further development of advanced Zn-MnO 2 batteries.